Asymmetric price transmission within the Portuguese stock market - Menezes, R.; Dionísio, A.; Mendes, D.A. (Physica A, 2004)
This paper uses threshold autoregressive (TAR) and momentum threshold autoregressive (M-TAR) models to address the problem of asymmetry within the Portuguese stock market. These asymmetric error correction models extend the original cointegration models to deal with the problem of low power of unit roots and cointegration tests in the presence of asymmetric adjustment.